The Role of Family and School in Limiting Violence Phenomenon Against Children A Field Study in Lattakia Governorate - Tayoub, Mohammad; Salmoun, Reem; Ahmad, Safaa Hikmat (Latakia University Journal - Economic and Legal Sciences Series, 2019)
العنف ضد الأطفال: هو شكل من أشكال العنف, أو الضرر, أو الإساءة البدنية, أو العقلية والإهمال, أو إساءة المعاملة والاستغلال, بما في ذلك الإساءة الجنسية. ولتوصيف هذه الظاهرة من حيث أسبابها, وآثارها, ولمعرفة حجمها الحقيقي, أجرينا استقصاء ميداني من خلال استبيان يتضمن 72 سؤالاً حولها, وزعت على 400 أسرة في ريف ومدينة اللاذقية, وعولجت البيانات باستخدام حزمة برامج إحصائية: SPSS10, وتم اختبار صدق الاستبيان باستخدام معامل ارتباط سبيرمان براون, وكانت قيمتهR=0.802 وهي دالة إحصائيا. وقد اتبع المنهج الوصفي التحليلي في البحث وأهم ما خلص إليه1- إن الفقر والجهل من أهم الأسباب التي تدفع الأهل لاستخدام العنف 2- وإنّ للمدرسة والأهل معاً دوراً هاماً في بناء شخصية الطفل. وفي نهاية البحث اقترحنا تصميم برامج تدريبية لمساعدة الأهل على ضبط انفعالاتهم, وإنشاء عيادات نفسية للتخفيف من الآثار النفسية والسلوكية للعنف على الأطفال. وأن تقوم التربية المدرسية بدورها الهام في نشر الوعي بالطرق التربوية السليمة. Violence against children is a kind of aggression or damage; physical or mental abuse, as well as sexual abuse. To study this phenomenon, its causes and results, to know its real status, we conducted a field survey via a 72- question questionnaire about it, distributed to 400 households in Lattakia city and its countryside. Data were analyzed by using statistical package such as SPSS10. The validity of the data was tested by Spearman-Brown. Its value was R=0.802, which is statistically significant. The descriptive analytical method was conducted in this research, which concluded that poverty and ignorance1- were of the most important reasons that make a family use violence2-. Both school and parents have a role in building the personality of a child. We proposed training programs to help parents to control their feelings, create psychological clinics to lessen the psychological and behavioral effects of violence against children, and the school should have its role in spreading awareness of the sound educational methods.